2018
DOI: 10.1038/s41386-018-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases mediate GABAA receptor expression, physiology, and behavioral maladaptations in rat models of alcohol dependence

Abstract: Alcohol use disorders are chronic debilitating diseases characterized by severe withdrawal symptoms that contribute to morbidity and relapse. GABA receptor (GABAR) adaptations have long been implicated in the chronic effects of alcohol and contribute to many withdrawal symptoms associated with alcohol dependence. In rodents, GABAR hypofunction results from decreases in Gabra1 expression, although the underlying mechanism controlling Gabra1 expression after chronic ethanol exposure is still unknown. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 68 publications
4
34
0
Order By: Relevance
“…or TSA (2 mg/kg, in 10% DMSO in 0.9% saline i.p. ; Selleck Chem Inc.) 2 hours prior to gavage on the last 2 days of treatment as well as a third injection two hours prior to sacrifice, consistent with previously described methods (Pandey et al, 2008, Sakharkar et al, 2012, Bohnsack et al, 2018. While any potential effect of TSA on ethanol metabolism or clearance was not explicitly evaluated in this study, the fact that all recordings occurred 24 hours postadministration and that total ethanol clearance is typically observed 8-10 hours after administration with the gavage model make it unlikely that residual ethanol was present during recordings.…”
Section: Animal Use and Treatmentsupporting
confidence: 56%
See 1 more Smart Citation
“…or TSA (2 mg/kg, in 10% DMSO in 0.9% saline i.p. ; Selleck Chem Inc.) 2 hours prior to gavage on the last 2 days of treatment as well as a third injection two hours prior to sacrifice, consistent with previously described methods (Pandey et al, 2008, Sakharkar et al, 2012, Bohnsack et al, 2018. While any potential effect of TSA on ethanol metabolism or clearance was not explicitly evaluated in this study, the fact that all recordings occurred 24 hours postadministration and that total ethanol clearance is typically observed 8-10 hours after administration with the gavage model make it unlikely that residual ethanol was present during recordings.…”
Section: Animal Use and Treatmentsupporting
confidence: 56%
“…More recently, we have also shown that such alterations in GABA A subunit expression are at least partially governed by epigenetic mechanisms, as chronic ethanol treatment results in diminished Gabra1 expression that correlates with diminished acetylation of the Gabra1 promoter. Further, treatment with histone deacetylase (HDAC) inhibitors has been shown effective at preventing these ethanolinduced phenomena (Bohnsack et al, 2018). While compelling, a number of questions remain, namely: 1.…”
Section: Introductionmentioning
confidence: 99%
“…The studies show that EtOH induces adaptations in both synaptic and extrasynaptic GABA A receptor expression and/or function in cortex, hippocampus, and central amygdala in various animal models of dependence. Overall, there is a loss of GABAergic inhibition, manifest by losses in both phasic inhibition and tonic inhibition, tolerance to EtOH, and cross‐tolerance to benzodiazepines and other sedative hypnotics acting on GABA A receptors at the cellular level (Bohnsack et al, ; Kumar et al, ; Olsen and Liang, ). As a result of this growing body of evidence, we and others have proposed that EtOH addiction evolves in response to a loss of GABAergic inhibition across the brain that results in an imbalance in excitatory and inhibitory signaling, leading to loss of control over neural firing in a plethora of circuits that regulate behavioral control of alcohol seeking and intake.…”
Section: Alcohol Addiction Results From Loss Of Gabaa Receptor‐mediatmentioning
confidence: 99%
“…We have recently observed that the impaired inhibition in amygdala by chronic stress is primarily due to the loss of tonic inhibition (Liu et al, 2014), which is mediated by extrasynaptic GABA A Rs, rather than the phasic inhibition by synaptic GABA A Rs. Notably, both preclinical and clinical evidence has demonstrated that GABAergic disinhibition is highly linked to the pathogenesis of multiple neuropsychiatric diseases (Brambilla et al, 2003;Bohnsack et al, 2018;Zhang et al, 2018) and the therapeutic effect of many anxiolytic agents acts at least partially through augmenting GABAergic inhibition in amygdala (Nuss, 2015). Thus, understanding the precise mechanisms underlying stressinduced GABAergic disinhibition in amygdala may yield novel targets for prevention and treatment of stress-related neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%